Methodological system for the formation of meta-subject skills of primary school students in the context of STEM education - Yesnazar, Assel; Zhorabekova, Ainur; Kalzhanova, Altynai; Zhuzimkul, Baiymbetova; Almukhanbet, Sholpan (Frontiers in education (Lausanne), 2024)
The significance of this study lies in fostering skills among school students that enables them to process information from several academic subjects, utilize science and technology at the same time, create new innovative projects, think critically and creatively, achieve meta-subject and personal outcomes, apply their abilities and knowledge to solve real-life problems, and make decisions based on current information utilizing available digital technologies. The main goal of this research is to propose a methodological system for the formation of meta-subject skills in primary school students in the context of STEM education. This framework encompasses several essential stages: a conceptual foundation for the formation of meta-subject skills of primary school students; methods of teaching through STEM; and interdisciplinary, meta-subject tasks and integrated projects aimed at fostering meta-subject skills. Moreover, the study describes an elective course program called “Secret of the World.” This course is intended for second grade learners and serves as a practical implementation of the proposed methodology. This course focuses on the promotion of integrated learning based on common topics, application of scientific and technical knowledge, enhancement of critical thinking and problem solving, stimulation of curiosity in science and technical subjects, and utilization of creative and innovative approaches to projects.